Avaliação do tipo de procedimento odontológico, cirurgia x dentística restauradora, na variabilidade do tempo de duração de dois anestésicos: bupivacaína x prilocaína - Santos, Lúcio Murilo dos [UNESP] (1997)
The local anesthetics due to because of the large use in dentistry have been motive of a great number of researchs, however the focus of these studies is the duration time, toxic effects and sistemic interactions. With this research we have the pourpose to observe if have alteration in the time of duration between two anesthetics when used with the same anesthetics techinic, but with distinct dental procedure. Two groups with 14 subjects each were formed: one with a necessity of lower wisdom teeth surgery, and the other that need restourative dentistry. The results obtained were analysed by the Blox-Plot diagram, t test of Student and Mann-Whitney test. The data analysis show that have a significative variability of the duration time of bupivacaine and prilocaine, but all the datas are include in the same group; the duration time of both anesthetics don't follow the normal distribution courve; the anesthetic duration of bupivacaine 0,5% with epinephrine I: 200.000 is, in the median study, 2,2 major time that the prilocaine 3% with felipressin 0,03 UI/ml; and that the odontologic procedure mode, make no difference in the variability of duration time of two anesthetics used in this study